Risk factors for health impairments in children after hospitalization for acute COVID-19 or MIS-C - Maddux, Aline B.; Young, Cameron C.; Kucukak, Suden; Zambrano, Laura D.; Newhams, Margaret M.; Rollins, Caitlin K.; Halasa, Natasha B.; Gertz, Shira J.; Mack, Elizabeth H.; Schwartz, Stephanie; Kong, Michele; Loftis, Laura L.; et al. (Frontiers in Pediatrics, 2023)
Objective: To identify risk factors for persistent impairments after pediatric hospitalization for acute coronavirus disease 2019 (COVID-19) or multisystem inflammatory syndrome in children (MIS-C) during the SARS-CoV-2 pandemic. Methods: Across 25 U.S. Overcoming COVID-19 Network hospitals, we conducted a prospective cohort study of patients <21-years-old hospitalized for acute COVID-19 or MIS-C (May 2020 to March 2022) surveyed 2- to 4-months post-admission. Multivariable regression was used to calculate adjusted risk ratios (aRR) and 95% confidence intervals (CI). Results: Of 232 children with acute COVID-19, 71 (30.6%) had persistent symptoms and 50 (21.6%) had activity impairments at follow-up; for MIS-C (n=241), 56 (23.2%) had persistent symptoms and 58 (24.1%) had activity impairments. In adjusted analyses of patients with acute COVID-19, receipt of mechanical ventilation was associated with persistent symptoms (aRR 1.83 [95% CI: 1.07, 3.13]) whereas obesity (aRR 2.18 [95% CI: 1.05, 4.51]) and greater organ system involvement (aRR 1.35 [95% CI: 1.13, 1.61]) were associated with activity impairment. For patients with MIS-C, having a pre-existing respiratory condition was associated with persistent symptoms (aRR 3.04 [95% CI: 1.70, 5.41]) whereas obesity (aRR 1.86 [95% CI: 1.09, 3.15]) and greater organ system involvement (aRR 1.26 [1.00, 1.58]) were associated with activity impairments. Discussion: Among patients hospitalized, nearly one in three hospitalized with acute COVID-19 and one in four hospitalized with MIS-C had persistent impairments for >2 months post-hospitalization. Persistent impairments were associated with more severe illness and underlying health conditions, identifying populations to target for follow-up.